Alternative Teacher Preparation Programs: Examination Through a Marketing Lens. (September 2019) - Chamberlin-Kim, Janet; Tarnay, Jennifer; Wells, Jenny C.
This investigation used the 7 P's Service Marketing Mix (i.e., product, price, place, promotion, people, physical evidence, and processes) to review development and recruitment strategies of special education alternative teacher preparation programs. Articles published between 1997 and 2018 were reviewed to identify alternative teacher preparation programs developed to tackle the chronic teacher shortage in special education across the United States. A total of 17 articles met the inclusion criteria, 10 of which specifically targeted rural areas. Results indicated people (94%), place (94%), and product (88%) were most consistently addressed in program design. However, price (59%) and promotion (41%) were addressed least. Overall, 1, 419 teacher candidates were recruited into the 17 special education alternative teacher preparation programs, with 460 recruited from rural areas.